Electron excitation of the 41P1 state of a zinc atom - Piwinski, M.; Klosowski, L.; Dziczek, D.; Chwirot, S.; Das, T.; Srivastava, R.; Stauffer, A; Bostock, Christopher; Fursa, Dmitry; Bray, Igor (American Physical Society, 2012)
Experimental results of Stokes parameters and electron-impact coherence parameters for excitation of 4 1P1 state of zinc atoms are presented. The electron-photon coincidence method in the coherence-analysis version was applied to obtain data for scattering angles in the range from 5° to 40° for incident electron energy 100 eV. The experimental results are presented together with convergent-close-coupling-method and relativistic-distorted-wave-approximation theoretical predictions.